Respuesta :

→ 6x² - 2x - 20

→ 6x² + 10x - 12x - 20

→ x(6x + 10 ) - 2 (6x + 10)

→ (6x + 10) (x - 2) .

for

6x - 10 = 0

6x = 10

[tex]{x\:=\:\frac{5}{3}}\\[/tex]

for x - 2

x = 2

The factored form of the expression is (6x+10)(x-2)

How to factorize expression

Give the quadratic expression

6x^2 -2x -20

On factorizing

6x^2 -2x -20

6x^2 -12x + 10x -20

6x(x-2) + 10(x-2)

(6x+10(x-2)

HEnce the factored form of the expression is (6x+10)(x-2)

Learn more on factorization here: https://brainly.com/question/25829061